MAKNA NISYᾹN DALAM AL-QUR’AN KAJIAN SEMIOTIKA CHARLES SANDERS PIERCE - Rizal, Teuku Muhammad; Maula Sari (IAIN Madura, 2022)
This researcher discusses the meaning of nisyān in the Al-Qur'an by using the semiotic analysis of Charles Sanders Perice. This library research used the mauḏû'î (thematic) method by collecting verses which are derivation of the word nisyān. Descriptive analysis was used to describe the data on the interpretation of the Al-Qur'an through the semiotic analysis of Charles Sanders Peirce. Semiotic Charles' theory is famous for his trichotomy; sign, object, and interpretant. This research revealed, based on the object, the meaning of nisyān are things that are intentional in the form of Aqidah. Substantially, all forms of objects are human intentional elements which God will judge against humans. The result of Charles Sanders Peirce's semiosis by placing the word nisyān as a representative that is qualisign in the form of an initial sign related to objects (sinsigns) in the form of things that are intentional by humans related to aqidah, resulting in the interpretant